Students’ perception of an Arabic language course in humanities degree programmes at the International Islamic University Malaysia - Mohammad Lotfie, Maskanah; Zubir, Badri Najib; Md Ghalib, Mohd. Feham (IDOSI Publication, 2013)
This study is an investigation of students’ perception of an Arabic language course taught to humanities undergraduates at the International Islamic University Malaysia (IIUM). The course, LQ 2046, is a graduation requirement taken by students after passing three lower levels of Arabic proficiency courses. The study utilised a questionnaire that was administered to students enrolled in the course. A total of 180 participants responded to 104 items on attitude towards the course, teaching techniques, teaching and learning processes, textbook as well as reading sub-skills. The students also responded to an open-ended section that sought their views and suggestions about the course. It was found that the students’ perception of the course was largely positive but they opined that a communication-based syllabus could be more beneficial for employment purposes. These findings are important in determining the future direction of the Arabic language courses for humanities students.